URBAN MEMORY, RENOVATION AND ECONOMIC SPACE: LOCAL RESIDENTS AND IMMIGRANTS IN IRAN - Shalchi, S.; Mohabbati, F. (ВЕСТНИК ЧЕЛЯБИНСКОГО ГОСУДАРСТВЕННОГО УНИВЕРСИТЕТА, 2022)
Urban memory, as an arena for remembering the past, exists in urban networks and interactions of cities and lays the foundation for actions and for organizing relations with cultural groups. Urban memory is an arena based on which the residents organize social and economic relations with other ethnic–cultural groups. Hence, contrary to the dominant memory and macro ideologies, memory similes exist in neighborhoods offers a unique interpretation of urban life. This research was conducted in Kan neighborhood as the one with an urban-rural fabric. The results demonstrate how the village is restricted to a small neighborhood during renovation plans. It also shows how immigrants have been gradually enabled to produce and reproduce their economic and social spaces in Kan.